2007
DOI: 10.1088/0022-3727/40/21/021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spatial changes in broadening on self-absorbed lines and its impact on plasma diagnostics

Abstract: The influence of the spatial dependence of the line profile on the shape of a line with asymmetric self-reversal emitted from inhomogeneous discharge plasmas is investigated by solving the equation of radiative transfer using relative distribution functions for the source function and the line broadening including complex overlapping lines. The theoretical results show that the features of an asymmetric lineshape are related to the broadening mechanisms and enable us to infer from the recorded line the dominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…The self-absorbed 396.15 nm resonant line exhibits a peak at its central wavelength. Such a feature has been already reported 24,27 in the case of sodium resonant transitions in a high pressure ͑0.7-2.9 bars͒ lamp discharge. However, the populating processes and spectral broadening mechanisms are strongly different from ours: the temperature is about 1000 K, the atomic density ranges from 10 24 to 10 25 m −3 , and the electron density from 10 21 to 10 22 m −3 .…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…The self-absorbed 396.15 nm resonant line exhibits a peak at its central wavelength. Such a feature has been already reported 24,27 in the case of sodium resonant transitions in a high pressure ͑0.7-2.9 bars͒ lamp discharge. However, the populating processes and spectral broadening mechanisms are strongly different from ours: the temperature is about 1000 K, the atomic density ranges from 10 24 to 10 25 m −3 , and the electron density from 10 21 to 10 22 m −3 .…”
Section: Introductionsupporting
confidence: 73%
“…The self-absorbed lines emitted by such plasmas have been the subject of several works. [22][23][24] In another paper, 25 we derived realistic spatial profiles and time evolutions of plasma densities at low background pressure ͑5 Pa͒ from the analysis of the aluminum of 308.21 and 3096.15 nm resonant transitions, and we showed that the LIP state is clearly out of equilibrium. We also investigated aluminum LIPs under atmospheric standard conditions by achieving dual-laser absorption experiments.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Reproducing this profile as a function of p by spectrally resolved radiative-transfer calculations will probably be very difficult, especially for different positions in the arc 47 or even for the position-averaged spectra that we measured. On the other hand, understanding the profile quantitatively might give new insights on the fundamental atomic and molecular line-broadening mechanisms at UHP conditions.…”
Section: Discussionmentioning
confidence: 99%
“…1 In the vicinity of the transition frequency, although the radiances calculated from the equation of radiation transport are practically zero, the measured values can differ from zero quite appreciably. Especially, in resonance lines an additional peak is usually formatted in place of the reversal minimum.…”
mentioning
confidence: 92%